2013
DOI: 10.1007/s11042-013-1612-8
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical model for gamification of learning (DMGL)

Abstract: The purpose of this paper is to hypothesize 'Dynamical model of educational effectiveness for the gamification of learning, and to widely announce a pure and right function of game through our model. For the theoretical contribution of gamification, we propose a dynamical model of game based learning that aims to maximize educational effectiveness that correlates with the four main primary factors (curiosity, challenge, fantasy and control). The main idea of this model is based on the correlations of four fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
0
15

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(119 citation statements)
references
References 13 publications
1
83
0
15
Order By: Relevance
“…Para determinar los cambios en las necesidades particulares de los alumnos dentro del proceso de gamificación se han precisado modelos procedentes del diseño motivacional (Kim y Lee, 2015;Cheong, Cheong y Filippou, 2013) y del diseño instruccional (Matejka, Li, Grossman y Fitzmaurice, 2012;McGrath y Bayerlein, 2013). Los resultados obtenidos demuestran su provecho en la evaluación de estímu-los y en la promoción de actividades que no dependan de la motivación extrínseca.…”
Section: Gamificación En Contextos Educativosunclassified
See 1 more Smart Citation
“…Para determinar los cambios en las necesidades particulares de los alumnos dentro del proceso de gamificación se han precisado modelos procedentes del diseño motivacional (Kim y Lee, 2015;Cheong, Cheong y Filippou, 2013) y del diseño instruccional (Matejka, Li, Grossman y Fitzmaurice, 2012;McGrath y Bayerlein, 2013). Los resultados obtenidos demuestran su provecho en la evaluación de estímu-los y en la promoción de actividades que no dependan de la motivación extrínseca.…”
Section: Gamificación En Contextos Educativosunclassified
“…No obstante, los modelos de gamificación vinculados al proceso educativo representan más de la mitad de la muestra de la última criba: 10 artículos (58%), entre los cuales se encuentran: Nolan y McBride (2013); Schoech, Boyas, Black y Lambert (2013); Mettler y Pinto (2015); Hamzah, Ali, Saman, Yusoff y Yacob (2015); Kim y Lee (2015); y Tomé, da Cunha, Farias, Rosa, Anton y Gasparini (2015). No obstante, estos últimos dos modelos mencionados se presentan como los únicos en evidenciar con meridiana claridad su orientación hacia entornos e-learning, demostrando su efectividad frente a entornos de enseñanza tradicional y especificando la proveniencia de cada una de sus variables.…”
Section: Taxonomías De La Gamificación En La Literatura Científicaunclassified
“…Lin et al [4] investigated the potential benefits of using animation, visual cueing, and their combination in a multimedia environment designed to support learners" acquisition and retention of scientific concepts and processes, concluding that participants provided with animations retained significantly more concepts than their peers provided with static graphics. Kim et al [5] explored the effects of gamification of learning and concluded that after some period of adaptation the learning curve is quite steeper that with regular learning. This list goes much further and similar conclusions are presented in many other researches, such as: Arcelli et al [6], Mayer et al [7], Lou et al [8], Aloraini [9], Milovanovic et al [10], Mercier et al [11], Pé rez-López et al [12], Barra et al [13], Surjono et al [14], Rabah [15], Tibbitts et al [16], Cuban et al [17], Evans et al [18], Gilakjani [19], Khoo [20] [47], Schweppe et al [48], that undoubtedly prove the benefits gained by the implementation of multimedia technologies in education.…”
Section: Motivation and Related Workmentioning
confidence: 99%
“…Many of them use pretty simple technologies such as implemented plug-ins based on rewarding techniques (Kim and Lee, 2013). Those gamification techniques strive to leverage people's natural desires for socializing, learning, competition or achievement.…”
Section: Overview Of Technological Aspects Of the Gamification Modelmentioning
confidence: 99%